Modeling and Analysis on the Evolution Process of Tool Working Angle in Gear Skiving Process - Yongpeng Chen; Hongliang Liu; Yong Yang (Jixie chuandong)
Gear skiving is an efficient gear cutting technology，and the tool working angle is an important parameter affecting the cutting performance. Due to the involving complex kinematics relation and cutting tool geometry in skiving process，tool working angle changes continuously and is affected by several factors. Primarily，the kinematics model is established based on gear skiving principle and coordinate transformation method. And the mathematical model which specifying the forming flank，rake face and cutting edge of the skiving cutter is proposed according to the geometric configuration of skiving cutter. The calculation formulas of the working rake angle and relief angle of the skiving cutter are derived by bringing in the definition of tool working angle in oblique cutting model. It is capable of realizing analytically express the evolution process of the working angle of gear skiving cutter. Finally，the influence of the designed rake angle and the helix angle of the skiving cutter on the working angle is analyzed. The results show that the designed rake angle tends to affect the working rake angle，while the helix angle of skiving cutter is more conducive to the relief working angle，and the analysis results can provide theoretical support for tool structure optimization for skiving cutter.